Causality Teaching Application on Criminal Actions Due to Death Case in Hospital Over Decision of Supreme Court Indonesia Republic No. 1110 K/Pid.Sus/2012 - Jonhardivivera Sembiring; Ahmad Sofian (Penerbit Kemala Indonesia, 2021)
Health services basically aim to carry out efforts to prevent and treat a disease, including medical services based on an individual relationship between a doctor and a patient. Doctors are parties who have expertise in the medical field who are considered to have the ability and expertise to perform medical actions. Meanwhile, patients are sick people who are common with their illness and entrust themselves to be treated and cured by doctors. Therefore, doctors are obliged to provide the best possible medical service for patients. But in medical services there are times when it doesn't work and the patient is pronounced dead. This phenomenon can lead to prosecution of the doctor or other health personnel for the death of the patient. This research was conducted to find out how the application of causality teaching in criminal acts that resulted in the death of patients due to medical action. In addition, this research also conducted to find out how the application of causality teaching to crimes that caused death in the Supreme Court Decision Number 1110 K / Pid.Sus / 2012. To examine this, the author uses a normative legal research method and uses a statutory approach by referring to the applicable legal rules. Based on the results of the research it was found that the public prosecutors, judges and legal advisors in seeing a case had different points of view. The public prosecutors saw the defendants' mistakes from all aspects by using the teaching of causality conditio sine qua non, while from the point of view of the legal advisor as a defence the teaching of causality objective generalization and the judge as a case breaker uses the teaching of causality novus actus interveniens.